Utilidad diagnóstica del CA125 y HE4 para la determinación de cáncer ginecológico - Panimboza Yanzapanta, Alexandra Maribel (2022)
ABSTRACT: Tumor markers are substances or processes released by cancer cells or other cells in the body that are produced in response to cancer or certain benign conditions or pathologies. This research aims to investigate the diagnostic utility of CA125 and HE4 for the determination of gynecological cancer. The methodology used in this work was a qualitative approach, at descriptive level, documentary design, cross-sectional and retrospective, using a population of 50 useful bibliographic sources related to the study object, for the development of inclusion and exclusion criteria 40 bibliographic sources were taking and applied also information from websites, epidemiological reports, digital manuals and scientific articles published in Elsevier, Scielo, Redalyc and Medigraphic, published over the last 10 to carry out the current criteria. To obtain data, the search strategy was applied over databases and web search engines. The results obtained were that the HE4 test of this study confirm the high sensitivity and specificity of this molecule on CA125 for ovarian cancer, thus presenting a sensitivity of 91% versus 83% and a specificity of 75% versus 67%, which makes them feasible for use as effective tumor markers for the identification of the presence of ovarian cancer, recommended as a diagnostic or prognostic indicator and monitoring of disease treatment after ovarian cancer surgery and chemotherapy.